Role of extracellular vesicles in cancer: implications in immunotherapeutic resistance - Wang, Shuai; Wang, Zerui; Liu, Min; Sun, Xiyang (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs) are lipid membrane-bound vesicles involved in cell-cell communication, particularly in the context of cancer. Immunotherapy, a rapidly evolving field in oncology, is a type of cancer treatment relying on the body’s own immune system to fight mutated cancer cells. Recently, the significance of immunotherapeutic resistance has been increasingly acknowledged owing to the heightened prevalence of cancer and its commonly advanced stage upon diagnosis. However, the complexity and heterogeneity of tumor cells pose challenges to immunotherapy, and the role of EVs in immunotherapeutic resistance remains unclear. Recent studies focused on the role of EVs as heterogeneous groups of nanoparticles in intercellular communication, particularly within the tumor microenvironment (TME). EVs, which include exosomes, shed microvesicles, while apoptotic bodies carry a diverse range of molecular cargo, including proteins, nucleic acids, lipids, and other bioactive molecules. The complexity and versatility of EVs make them a fascinating area of study, with promising implications for the future of immunology and medicine. This brief review highlights the involvement of EVs in immunotherapeutic resistance (e.g., PD-L1 transfer, miRNA-mediated pathways) with a focus on their biogenesis, secretion, and functional roles in cancer, underscoring their potential as diagnostic and therapeutic tools.